2021
DOI: 10.1038/s41598-021-90452-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent transition from islet insulin hypersecretion to hyposecretion in mice with the long QT-syndrome loss-of-function mutation Kcnq1-A340V

Abstract: Loss-of-function (LoF) mutations in KCNQ1, encoding the voltage-gated K+ channel Kv7.1, lead to long QT syndrome 1 (LQT1). LQT1 patients also present with post-prandial hyperinsulinemia and hypoglycaemia. In contrast, KCNQ1 polymorphisms are associated with diabetes, and LQTS patients have a higher prevalence of diabetes. We developed a mouse model with a LoF Kcnq1 mutation using CRISPR-Cas9 and hypothesized that this mouse model would display QT prolongation, increased glucose-stimulated insulin secretion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Islets carrying the LoF mutation on both alleles hypersecreted insulin in response to glucose ex vivo at a young age (12‐14 weeks). Yet when performing the same experiments 10 weeks later, at 24 weeks of age, islets heterozygous and homozygous for the mutation now secreted less insulin in response to glucose compared to their littermate controls 53 . This transition from hyper‐ to hyposecretion of insulin is reminiscent of the phenotype described in KCNH6 / Kcnh6 LoF in humans and mice 58 and may explain the combination of hyperinsulinaemia 4,5 and diabetes 6 in patients with LQTS.…”
Section: Kcnq1 Long Qt Syndrome and The Development Of Diabetesmentioning
confidence: 84%
See 3 more Smart Citations
“…Islets carrying the LoF mutation on both alleles hypersecreted insulin in response to glucose ex vivo at a young age (12‐14 weeks). Yet when performing the same experiments 10 weeks later, at 24 weeks of age, islets heterozygous and homozygous for the mutation now secreted less insulin in response to glucose compared to their littermate controls 53 . This transition from hyper‐ to hyposecretion of insulin is reminiscent of the phenotype described in KCNH6 / Kcnh6 LoF in humans and mice 58 and may explain the combination of hyperinsulinaemia 4,5 and diabetes 6 in patients with LQTS.…”
Section: Kcnq1 Long Qt Syndrome and The Development Of Diabetesmentioning
confidence: 84%
“…During an OGTT patients with LQT1 showed hypersecretion of insulin which resulted in symptomatic hypoglycaemia ~3‐5 hours after the glucose load. Follow‐up studies in mice with a clinically relevant LoF mutation in Kcnq1 showed that the hypersecretory phenotype was also present ex vivo 53 . This suggests that the hypersecretion of insulin found in the setting of KCNQ1/Kcnq1 LoF is because of an effect in the beta cell itself and/or in the other endocrine cells of the pancreatic islet, but not from effects occurring outside of the pancreas.…”
Section: The Role Of Delayed Rectifier K+ Channels In the Pancreatic ...mentioning
confidence: 95%
See 2 more Smart Citations
“…The authors proposed a combined mechanism of islet overgrowth due to the proproliferative effect of the paternal imprint pattern of the 11p15 region together with a lack of expression of the KCNQ1 voltage-gated potassium channel that is expressed only from the maternal allele. KCNQ1 itself is assumed to be involved in the regulation of potassium flux in pancreatic β cells [ 15 ]. Pancreatic histology in patients with CHI and BWS due to UPD11p shows a marked diffuse increase in the volume of endocrine tissue, often with a gradient in the degree of islet expansion across the entire pancreas [ 14 ].…”
Section: Discussionmentioning
confidence: 99%